The roles of m6A RNA modifiers in human cancer. Issue 3 (March 2020) - Liang, Yanwen; Zhan, Guankai; Chang, Kao-Jung; Yang, Yi-Ping; Wang, Lingfang; Lin, Jiebo; Hsu, Chih-Hung
Abstract : Like DNA and proteins, RNA is subject to numerous (over 160) covalent modifications which play critical roles to regulate RNA metabolism. Among these modifications, N 6 -methyladenosine (m 6 A) is the most prevalent RNA methylation on mRNA which occurs on around 25% of transcripts. The recent studies demonstrated that m 6 A participates in many aspects of RNA processing, including splicing, nuclear exporting, translation, stabilization, etc. Therefore, it revealed a new layer of regulatory mechanism for gene expression and has been termed "RNA Epigenetics" or "Epitranscriptomics". RNA m 6 A is regulated and exerts its functions by three groups of "m 6 A RNA modifiers" including m 6 A methyltransferases (writers), m 6 A demethylases (erasers), and m 6 A binding proteins (readers). In this review, we would summarize and discuss the current understandings of the roles of the conventional m 6 A RNA modifiers in human cancers.